Intraperitoneal supplementation of iron alleviates dextran sodium sulfate-induced colitis by enhancing intestinal barrier function - Li Liang (Elsevier, 2021)
Iron supplementation is necessary for the treatment of anemia, one of the most frequent complications in inflammatory bowel disease (IBD). However, oral iron supplementation leads to an exacerbation of intestinal inflammation. Gut barrier plays a key role in the pathogenesis of IBD. The aim of this study was to characterize the interrelationship between systemic iron, intestinal barrier and the development of intestinal inflammation in a dextran sulfate sodium (DSS) induced experimental colitis mice model. We found that DSS-treated mice developed severe inflammation of colon, but became much healthy when intraperitoneal injection with iron. Iron supplementation alleviated colonic and systemic inflammation by lower histological scores, restorative morphology of colonic villi, and reduced expression of pro-inflammatory cytokines. Moreover, intraperitoneal supplementation of iron enhanced intestinal barrier function by upregulating the colonic expressions of tight junction proteins, restoring intestinal immune homeostasis by regulating immune cell infiltration and T lymphocyte subsets, and increasing mucous secretion of goblet cells in the colon. High-throughput sequencing of fecal 16 S rRNA showed that iron injection significantly increased the relative abundance of Bacteroidetes, which was suppressed in the gut microbiota of DSS-induced colitis mice. These results provided evidences supporting the protective effects of systemic iron repletion by intraperitoneal injection of iron on intestinal barrier functions. The finding highlights a novel approach for the treatment of IBD with iron injection therapy.